SULFATION PATHWAYS: A role for steroid sulphatase in intracrine regulation of endometrial decidualisation. (August 2018) - Gibson, Douglas A; Foster, Paul A; Simitsidellis, Ioannis; Critchley, Hilary O D; Kelepouri, Olympia; Collins, Frances; Saunders, Philippa T K
Abstract : In women, establishment of pregnancy is dependent upon 'fine-tuning' of the endometrial microenvironment, which is mediated by terminal differentiation (decidualisation) of endometrial stromal fibroblasts (ESFs). We have demonstrated that intracrine steroid metabolism plays a key role in regulating decidualisation and is essential for time-dependent expression of key factors required for endometrial receptivity. The primary aim of the current study was to determine whether sulphated steroids can act as precursors to bioactive sex steroids during decidualisation. We used primary human ESF and a robust in vitro model of decidualisation to assess the expression of genes associated with sulphation, desulphation and transport of sulphated steroids in human ESF as well as the impact of the steroid sulphatase (STS) inhibitor STX64 (Irosustat). We found evidence for an increase in both expression and activity of STS in response to a decidualisation stimulus with abrogation of oestrone biosynthesis and decreased secretion of the decidualisation marker IGFBP1 in the presence of STX64. These results provide novel insight into the contribution of STS to the intracrine regulation of decidualisation.